1996
DOI: 10.1016/s1078-5884(96)80017-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of arterial stenoses in angioplasty surveillance: A comparison with angiography

Abstract: Restenosis should be assessed with imaging of the angioplasty site during angioplasty surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In some patients, clinical assessment alone cannot accurately diagnose arterial compromise10, 13, 14. Ankle : brachial pressure index (ABPI) measurement and venous imaging using colour venous duplex ultrasonography are validated methods of vascular assessment and can be performed during a single clinic visit15.…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, clinical assessment alone cannot accurately diagnose arterial compromise10, 13, 14. Ankle : brachial pressure index (ABPI) measurement and venous imaging using colour venous duplex ultrasonography are validated methods of vascular assessment and can be performed during a single clinic visit15.…”
Section: Introductionmentioning
confidence: 99%
“…62 The diagnostic potential of these measurements is uncertain. In a study 63 using a velocity ratio >2 to indicate stenosis of >50% 5 days post-procedure, arteries with a residual stenosis exceeding 50% had a significantly worse patency rate (11%) at one year compared with lower levels of residual narrowing, which had patency rates of 80%.…”
Section: Angioplasty and Stentsmentioning
confidence: 99%
“…They found that their primary patency at 1 year was a dismal 22%, leading them to the appropriate conclusion that long segment stent use in superficial femoral artery disease should be reserved for few patients. The optimal method of follow-up after angioplasty has attracted considerable attention, most recently from Nyamekye and associates from the Middlesex Hospital in London [31]. They found, remarkably, that neither symptoms, pulse status, resting ankle brachial index, nor exercise ankle brachial index showed any useful correlation with angiography.…”
Section: Iliac-femoral Angioplastymentioning
confidence: 99%